ANALISIS EFISIENSI DAN EFEKTIVITAS PENGGUNAAN MODAL KERJA PADA PERUSAHAAN SUB-SEKTOR ANEKA INDUSTRI ELEKTRONIKA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA PERIODE 2017-2019 - Bornok Situmorang; Megalia (Realible Accounting Journal, 2021)
This research aims to determine the level of efficiency and effectiveness of the use of working capital in various electronics industri sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. The analysis technique used in this research is to use the working capital turnover ratio by comparing sales to net working capital and the profitability ratio by comparing the profit margin with working capital. The type of research used is descriptive research using quantitative data as the basis of analysis. Based on the results of the study, it shows that the average level of efficiency and effectiveness in the use of working capital in various electronics industri sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017 - 2019 period is declared Efficient and Effective. Where it means that the higher the rate of working capital turnover will be the more income you get from that income stream. The higher the rate of working capital turnover, the more efficient and effective it is in the use of working capital.